Desert grey - Hayes, Esther Marlena, author; Altschul, Andrew, advisor; Ausubel, Ramona, committee member; Bowser, Gillian, committee member (Colorado State University. Libraries, 2021)
This collection of short stories and essays engages both the infertility of a landscape rendered unrecognizable by environmental change and the enduring fertility of the bodies that live there. The majority of the collection takes place in my first home—the deserts of Nevada. This is a landscape that has been abused both for its infertility and its fertility. It has been a site for nuclear tests and a dumping ground for waste; it has had tunnels carved into its mountains for the gold and the silver in its veins. In places real and invented, my characters—both real and invented—ask how to move forward. Will we be forgiven for what we have done?
Keywords: fiction; climate change; reproduction